The invention of coinage in the East and its first use in the West. Copies from the Gulf of Lion (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2021)
I think that the recent silver coins from the Gulf of Lyon, published  as Emporian coinage, must be interpreted as “copies”, “imitations”, of the coins of Massalia, Phocea and Mitilene circulating in that area during the transit of the 6th and 5th Centuries. The coins from these last mints,  scarce for the economic needs witnessed in Provence, Languedoc and Catalonia, led the Celtic, Gallic and Iberian communities to copy these Greek coins for commercial use. Of this use of money /currency in private spheres, we have  detailed testimonies in the leads written in Greek found in the same area, inscriptions that collect silver payments made according to the Gallic metrological system but adapted to the Phocean one, at least in the Pech-Maho lead.